Macromycetes determined in Baykan (Siirt) District - Keleş, Ali; Akçay, Mustafa Emre; Uzun, Yusuf; Sadullahoglu, Cemil; Kesici, Sedat (My University, 2024)
The current study was based on the macrofungi collected from Baykan (Siirt) district. As a result of field and laboratory studies, 88 species belonging to 56 families were identified. Nine taxa belong to Ascomycota and 79 to Basidiomycota. Considering the taxonomic categories of the species identified in the research area, it is seen that the order, family and genus represented by the most members are Agaricales, Agaricaceae and Agaricus L., respectively. The identified species are listed along with their localities, habitats/substrates, geographical positions, collection dates, and voucher numbers. All of the determined species are new records for the study area.
Keywords: Türkiye; Siirt; Biodiversity; macrofungi; Baykan